Combination vaccine - the importance and role in public health set up - Rahman. I., (Department Of Community Health, Faculty of Medicine, Universiti Kebangsaan Malaysia, 2000)
Infectious diseases are the world's leading cause of death. Vaccines have been shown to be the most cost-effective tool with demonstrable public health results in the form of decreased mortality and increased human survival. Advances in technology haveenabled the development of a whole range of new and improved vaccines. The successful combination of vaccines has opens up exciting prospects for present and future vaccine development. One of the major advantages of combination vaccines is the practicality of requiring one versus multiple injections. This in turn leads to a higher compliance and enhanced coverage needed for successful implementation of immunisation programme especially in the rural health set up. Combination vaccines have the potential to lower the overall cost of immunisation as the cost of immunisation is the cost of vaccination plus the cost of vaccine procurement, storage,transportation and delivery. Combination vaccines appear to be a public health cost effective solution.